Bipolar’s of Karang in the Novel Aku Tak Membenci Hujan by Sri Puji Hartini: Psychoanalysis - Wati, Ika Trisna Wati (JELP Journal of English Language and Pedagogy, 2025)
Multiple personality is a psychiatric illness. People who have multiple personalities can have two or even many personalities. The cause of multiple personality disorder is usually caused by trauma or painful events from childhood or adulthood. The purpose of this research is to describe the multiple personalities experienced by the character Karang in the novel “Aku Tak Membenci Hujan”, describe the causes of the multiple personality experienced by the character Karang in the novel “Aku Tak Membenci Hujan”, and describe the way Karang resolves the personality disorder he experiences. This study used a descriptive analysis method with a literary psychological approach. The literary psychology approach used comes from Sigmund Freud's psychological theory, namely psychoanalysis. The data used are in the form of words, phrases, and sentences that contain inner conflicts, the process of personality formation, and the form of multiple personality that is owned by Karang in the novel “Aku Tak Membenci Hujan”, which will be published in 2023. The data collection uses the reading and writing technique of the novel “Aku Tak Membenci Hujan”. The data were analysed using qualitative descriptive techniques using Sigmund Freud's psychoanalytic theory and the concept of multiple personality symptoms.